«METHOTREXATE ERA» IN CHILDREN RHEUMATOLOGY - S.R. Rodionovskaya; I.P. Nikishina ("Paediatrician" Publishers LLC, 2006)
This article sites modern principles and theoretical substantiation of pharmacotherapy by methotrexate in patients with juvenile arthritis. Particular emphasis has been placed on parenter al methods of drug introduction, as the possibility of therapy effectiveness increase. A variety of adverse reactions is outlined, recommendations on their monitoring and overcoming are made. The importance of duration and continuity of therapy is emphasized for the realization of disease modifying influence on clinical course. Algorithms of methotrexate use in various variants of juvenile arthritis are presented. Key words: methotrexate, juvenile arthritis, treatment, children.